2022
DOI: 10.1126/sciimmunol.abj8301
|View full text |Cite
|
Sign up to set email alerts
|

CD45RA + CD62L ILCs in human tissues represent a quiescent local reservoir for the generation of differentiated ILCs

Abstract: Innate lymphoid cells (ILCs) are highly plastic and predominantly mucosal tissue-resident cells that contribute to both homeostasis and inflammation depending on the microenvironment. The discovery of naïve-like ILCs suggests an ILC differentiation process that is akin to naïve T cell differentiation. Delineating the mechanisms that underlie ILC differentiation in tissues is crucial for understanding ILC biology in health and disease. Here, we showed that tonsillar ILCs expressing CD45RA lacked proliferative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Moreover, the authors demonstrated an accumulation of a CD62Lsubpopulation of CD45RA + ILCp in the inflamed mucosa of patients with both UC and CD. The expansion of CD26L -ILCp was found to be inversely proportional to the frequency of NKp44 + ILC3s, suggesting that disruptions to ILCp compartments may act to promote the disequilibrium of ILCs observed in IBD (67).…”
Section: Ilc1 In Intestinal Inflammationmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the authors demonstrated an accumulation of a CD62Lsubpopulation of CD45RA + ILCp in the inflamed mucosa of patients with both UC and CD. The expansion of CD26L -ILCp was found to be inversely proportional to the frequency of NKp44 + ILC3s, suggesting that disruptions to ILCp compartments may act to promote the disequilibrium of ILCs observed in IBD (67).…”
Section: Ilc1 In Intestinal Inflammationmentioning
confidence: 94%
“…While a question remains as to what extent this may impact IBD pathogenesis (65), it is notable that such a switch was additionally observed in the population of ILC precursors (ILCp); an increase in NKp44 + and CD56 + ILCp was detected in CD patients, coupled to a decrease in their corresponding naïve CD45RA + ILCp (64). However, while circulating human ILCp has been shown to contribute to the pool of ILCs in tissues (66), the extent to which perturbations in peripheral ILCp in IBD patents may impact the ILC compartment within the intestinal mucosae remains to be determined-for example, recent research has shown that CD45RA + ILCp exhibits tissue-specific differentiation potential (67). Moreover, the authors demonstrated an accumulation of a CD62Lsubpopulation of CD45RA + ILCp in the inflamed mucosa of patients with both UC and CD.…”
Section: Ilc1 In Intestinal Inflammationmentioning
confidence: 99%
“…It is suggested that the blood-circulating ILCPs could provide “on-demand” replenishment of ILC subsets in the inflamed sites as their niche to differentiate and propagate, which makes a clear contrast to naïve T cells in the lymph node (LN). However, ILCPs harbor differentiation potential into ILC subsets (e.g., ILC1/2/3 with T-bet/Gata-3/RORγt expression functionally reminiscent of Th1/2/17) and a quiescent state with reduced glycolysis and mitochondrial activity, without effector cytokine production or extensive proliferation, which all associate with the characteristics of naïve T cells ( 59 ). This tempts us to speculate that the biological significance of the blood-circulating ILCPs may be an innate counterpart of naïve T cells, which differentiate into helper and cytotoxic T cells of the acquired immune system.…”
Section: Variation Of the Ontogeny Of Ilcsmentioning
confidence: 99%
“…Claudin-2 transcriptional regulation analyses showed a significant role of interleukin 22 (IL-22) (10). IL-22 is usually produced at the site of inflammation by Th22, Th17, or innate lymphoid cell type 3 (11)(12)(13)(14)(15). It is a cytokine with double activity: 1) activates the immune system and 2) contributes to the enhanced production of extracellular matrix components.…”
Section: Introductionmentioning
confidence: 99%